Angular distribution and interception of diffuse solar radiation - Steven, M.D. (1977)
The estimation of the irradiance of sloping surfaces from standard meteorological measurements requires knowledge of the geometrical distribution of scattered radiation from the sky. Measurements of the radiance distribution of cloudless skies were made with a Linke-Feussner actinometer. When measurements of sky radiance N were expressed relative to the diffuse irradiance D of a horizontal surface, the angular distributions of N/D were remarkably independent of atmospheric turbidity. Standard distributions of N/D, drawn up for different solar zenith angles, were used to estimate the diffuse irradiance of slopes under cloudless skies. A new actinometer was designed for the measurement of the radiance of cloudy skies. A theoretical analysis of the energy budget of a thermopile in relation to the actinometer design is presented. Nine actinometers were used to measure mean distributions of radiance for partly cloudy and overcast skies. Results for overcast conditions indicated that the mean radiance near the horizon was larger than the value predicted by the 'Standard Overcast Sky' formula, but the increase in estimated irradiance of vertical surfaces was only about 2/16. A computer model was formulated for estimating the global irradiance of slopes using the new results for diffuse radiation. The model was applied to climatological mean radiation data from the Meteorological Office for Kew, Eskdalemuir, Aberporth and Lerwick.